Do drives drive the train of thought?: effects of hunger and sexual arousal on mind-wandering behavior - Rummel, Jan; Nied, Laura (Consciousness and cognition, 2017)
Physiological needs that are currently unfulfilled are known to affect human cognition and behavior. The present study investigates whether and how the temporary activation of two primary physiological needs, namely hunger and sexual arousal, influence both the frequency and the contents of mind-wandering episodes. To induce hunger, one group of participants fasted for a minimum of five hours whereas another group of participants was exposed to audio material with explicit sexual content to provoke sexual arousal. Both groups as well as an additional control group, which had not received hunger instructions and had not been exposed to arousing material of any kind beforehand, performed a reading task during which mind wandering was assessed using a standard experience-sampling method. Results showed that acute hunger but not elevated sexual arousal renders the occurrence of mind-wandering episodes more likely. Induction of both hunger and sexual arousal rendered the occurrence of need-related off-task thoughts more likely and changed time orientations of mind wandering. The present findings are well in line with the assumption that unfulfilled needs regularly achieve cognitive priority and extend the cognitive-priority idea to self-generated thoughts.